Exploring Innovative Teaching Strategies of the Singapore English Language Curriculum: A Learning Experience of Lesson Study - Wu, Lydia Fang; Razak, Abdul; Dashwood, Anna Maria (Journal of Language and Literature Studies, 2023)
The innovative teaching strategies employed within the context of Singapore's educational framework have been judiciously applied to enhance and enrich the English Language Curriculum. These have been strategically integrated into the pedagogical landscape of English language education. By infusing the English Language Curriculum with these innovative teaching strategies, educators and learners alike have been afforded a dynamic and progressive educational experience that transcends traditional paradigms. This study was conducted in a lesson study. The conducted Lesson Study unfolded across a meticulously orchestrated tripartite framework encompassing distinct research stages: training, instructional planning, and lesson observation. Initially, the data were subjected to a process of "open coding," as per the methodological tenets. Subsequently, a process of categorical organization ensued, wherein the data were systematically sorted into discrete categories. The finding showed that The intricate interplay between lesson study and curriculum innovation has unfolded as a symphonic harmonization that bridges the theoretical constructs of education with the practical realm of pedagogical implementation, immersing itself deeply within the crucible of the classroom.